Prosedur Evaluasi Pendidikan Islam - Ginanjar, Toni; Ulwiyah, Nur; Widjaja As’ad, M Zaimuddin (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The pettern of success in an educational program must follow assessment steps to measure the quality of educational institutions, learning, educational curriculum, teachers and students who are the center of attention in the world of education. The purpose of this research is to focus on the Islamic education evaluation procedure including planning, monitoring, data collection, data analysis and reporting of evaluation results. The research method uses library research (Library Research). Data collection technique with literature study, The type of data used using articles, scientific journals and books related to the discussion. And at the end of the research discussion, interesting results with conclusions. The results of this research are many steps that must be taken into account in the evaluation of Islamic education, as well as knowing the evaluation procedure in an applicative manner for better success in the future.